An Unlikely Refuge: Latvia's Women Volunteers in the Red Army in World War II. Issue 1 (February 2021) - Eglitis, Daina S.; Zelče, Vita
This article examines women's wartime experiences with a focus on Latvia's women volunteers in the Red Army in World War II. An estimated 8 percent of the Red Army was composed of women, who played a wide array of roles, including as snipers, combat engineers, medics, and frontline journalists. This level of female participation was unique in World War II, but a close examination of the phenomenon shows that motives and means for entry into the Red Army at the beginning of the war were not uniform. Our examination of the case of women volunteers from the Latvian Soviet Socialist Republic reveals key factors that fed women's fervent desire to "get to the front." It shows particular ways in which the Red Army functioned as an unlikely refuge, sheltering women from some of the hardships and threats of life in the Soviet Russian interior, including hunger, loneliness, and a lack of warm clothing, while providing a means of exacting revenge against a mortal enemy. At the same time, it exposed women to extremes of violence and conflict. Dominant Soviet narratives of women in war have presented them in largely marginal roles or have silenced stories that failed to comport with triumphalist and masculine representations of World War II. This work uses the voices of women volunteers in the Latvian Riflemen's Divisions of the Red Army to construct an agent-centered history of motives, experiences, and memories.